Case reportCholinergic urticaria – management and chosen aspects of aetiopathogenesis - Kowalczyk, Michał J.; Szramka, Beata; Prokop, Janusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Cholinergic urticaria is characterized by the appearance of hives, angioedema and itching triggered by an increase of skin temperature, e.g. after physical exercise. Here we describe a case of a 25-year-old male, who had been considered cured and whose symptoms reappeared. A few years’ experience in defying the disease has enabled us to come up with a number of pieces of advice for doctors and patients. Here we point to the synergy of H1 and H2 histamine receptor blockers, seasonal and daily cycles, and most important, ways of everyday management of symptoms such as adequate clothing. The newest findings in molecular biology concerning the issue of cholinergic urticaria and pointing to an antigen present in human sweat as the trigger in the process of mast cell degranulation are also described.